Associations of parental labour migration and childhood maltreatment with psychosocial health among adolescents and young adults in China - Yuwei Yang; Weiqing Jiang; Yitong He; Wanxin Wang; Yiling Hua; Cuihong Huang; Xinyu Zheng; Ciyong Lu; Xueying Du; Lan Guo (European Journal of Psychotraumatology)
Background: Few studies have simultaneously considered the impacts of parental labour migration and childhood maltreatment on psychosocial health.Objective: To estimate the complex associations of parental labour migration and childhood maltreatment with psychosocial health among adolescents and young adults in China.Method: This cross-sectional study was conducted among undergraduates aged 17 to 24 years from sixty colleges and universities across 10 provinces of China. Childhood maltreatment was assessed using the Childhood Trauma Questionnaire-Short Form, and psychosocial health was measured using the Strengths and Difficulties Questionnaire (SDQ). Weighted linear mixed regression models, multiplicative interactions, and joint and mediation analyses were performed.Results: Of the 28,810 participants included (mean [SD] age, 19.87 [1.62] years), 12035 (41.8%) were male. In the fully adjusted model, participants who experienced parental migration were more likely to report higher levels of SDQ total difficulties (e.g. β = 0.16 [95% CI, 0.05 to 0.28]) compared with those with non-migrant parents. A positive association was found between the cumulative number of childhood maltreatment and SDQ total difficulties (β = 0.54 [95% CI, 0.49 to 0.60]), with a dose-response relationship observed for the levels of childhood maltreatment and SDQ total difficulties. Compared with individuals without exposure to both parental migration and childhood maltreatment, those exposed to both parental migration and at least 2 numbers of childhood maltreatment had the highest magnitude of psychosocial health difficulties (β = 1.12 [95% CI, 0.91 to 1.33]). Moreover, childhood maltreatment may partially mediate the association between parental migration and psychosocial health, with the mediation proportion being 58.8%.Conclusion: Exposure to parental labour migration or childhood maltreatment was positively associated with psychosocial health among adolescents and young adults. Parental migration and childhood maltreatment may jointly aggravate psychosocial health problems. These findings indicate the necessity of comprehensive interventions targeting adversity stressors to improve psychosocial health, especially for left-behind children experiencing maltreatment.